IMPACT OF THE STRATEGIC STATEMENTS ADOPTED BY JORDANIAN PRIVATE UNIVERSITIES IN RELATION TO THEIR PERFORMANCE - Turgay, Tayfun; Alhawamdeh, Zead Mustafa (European Scientific Journal, ESJ, 2013)
This research set out to understand the disposition of Jordanian private universities with regards to competition, their preparedness to meet the global challenges posed by the highly competitive higher education industry, the competitive strategies they have adopted over the years and how it has impacted their regional and international performance After Conducting Literature review. This study develops two hypotheses. Applying a quantitative approach, it carried out structured content analysis on the strategic statements of the five universities which participated in the study of members of top level management of these universities and documented its findings. It then discussed the findings. The discussion section showed that with regard to the two hypotheses posed, this study found support for only hypothesis (2) and found an insignificant support for hypothesis (1). This implies that Jordanian universities considered the attainment of highest international standards both in infrastructural development and attracting foreign students and professors was important in countering the competitive challenges faced from local and international competitors. However, lack of support for hypotheses (1) implies that while private universities in Jordan have the intention to improve their image and meet international higher education standards, they had no road map to realize that ambition.